Flood-Rings Production Modulated by River Regulation in Eastern Boreal Canada - Nolin, Alexandre F.; Tardif, Jacques C.; Conciatori, France; Bergeron, Yves (Frontiers in Plant Science, 2021)
In northeastern boreal Canada long-term perspective on spring flooding is hampered by the absence of long gauge records. Changes in tree-ring anatomy of periodically flooded trees have allowed reconstruction of historical floods in unregulated hydrological systems. In regulated rivers, the study of flood rings could recover past flood history, assuming that the effects of hydrological regulation on their production can be understood. This study analyzes the effect of regulation on the flood ring occurrence (visual intensity and relative frequency) and on ring widths in Fraxinus nigra trees growing at five sites distributed along the Driftwood River floodplain. Driftwood River was regulated by a dam in 1917 that was replaced at the same location in 1953. Ring width revealed little to no evidence of the impact of river regulation, in contrast to the flood-rings. Prior to 1917, high relative frequencies of well-defined flood rings were recorded during known flood years, as indicated by significant correlations with reconstructed spring discharge of the nearby Harricana River. After the construction and the replacement of the dam, relative frequencies of flood rings and their intensities gradually decreased. Flood-ring relative frequencies after 1917 and particularly after 1953 were mostly composed of weakly defined (less distinct) flood rings with some corresponding to known flood years and others likely reflecting dam management. Strength of the correlations with the instrumental Harricana River discharge also gradually decrease starting after 1917. Compared to upper floodplain trees, shoreline trees at each site recorded flood rings less frequently following the construction of the first but especially of the second dam, indicating that water level regulation limited flooding in the floodplains. Compared to the downstream site to the dam, the upstream ones recorded significantly more flood rings in the post dam period, reemphasizing the importance of considering the position of the site along the river continuum and site conditions in relation to flood exposure. The results demonstrated that sampling trees in multiple riparian stands and along various hydrological contexts at a far distance of the dams could help disentangle the flooding signal from the dam management signal.